(untitled) (CIPEEX, 2024)
THIS BRIEF EXPLORES THE RAMIFICATIONS OF MISINFORMATION DURING THE COVID-19 OUTBREAK IN BRAZIL, WITH A FOCUS ON CIVIL LIABILITY ANALYSIS. IT INVESTIGATES THE LEGAL CONSEQUENCES OF THE SPREAD OF FAKE NEWS DURING THE PUBLIC HEALTH CRISIS AND HOW THIS HAS IMPACTED VARIOUS ASPECTS OF SOCIETY, INCLUDING REPUTATIONAL DAMAGE, SOCIAL PANIC AND EVEN LOSS OF LIFE DUE TO INACCURATE INFORMATION. THE STUDY IDENTIFIES CASES IN WHICH INDIVIDUALS AND MEDIA OUTLETS WERE HELD LEGALLY RESPONSIBLE FOR SPREADING FALSE INFORMATION, HIGHLIGHTING THE FLEXIBILITY OF THE BRAZILIAN LEGAL SYSTEM. THE RESEARCH UNDERLINES THE NEED FOR A COMPREHENSIVE APPROACH INVOLVING COLLABORATION BETWEEN THE PUBLIC SECTOR, SOCIAL MEDIA PLATFORMS AND CIVIL SOCIETY TO EFFECTIVELY COMBAT FAKE NEWS AND HIGHLIGHTS THE IMPORTANCE OF PUBLIC EDUCATION IN IDENTIFYING AND ADDRESSING DISINFORMATION.